(untitled) (Avaliação: Revista da Avaliação da Educação Superior, 2015)
In this paper we aim to contribute to the debate over accountability and assessment of higher education (HE) by introducing the Japanese system. We first discuss the circumstances and issues surrounding Japanese HE and then examine the historical development of the quality assurance and evaluation system. Since the 1990s, with the implementation of policies that focused on liberalization, deregulation and increased institutional autonomy, the role of the government has shifted from setting strict regulations and quality standards to organizing an evaluation system for assessing the learning outcomes and improving accountability of the HE institutions. Finally, we suggest how Japan may take hints from Brazil in organizing an evaluation system on a national level that can more efficiently support and assess HE institutions.